The Effects of dual task (fine motor precision + cognitive charge) on proprioception - Liutsko, Liudmila; Tous, Jose Maria; Segura, Sergi (Journal of Education Culture and Society, 2020)
The aim of the given preliminary study was to check whether any changes in fi ne motor behaviour exist in switching from single to double task (with cognition charge) in proprioceptive sensory graphomotor test conditions. Ten students (fi ve males and fi ve females), aged from 20 to 30 years old, took part in the experiment - precision of tracking of the models in both experimental test conditions: without and with cognitive task (counting numbers back). The variables for assessment were obtained with use of the digitalized proprioceptive diagnostics (Tous, 2008; Tous, J.M., Muiños, Tous, O., & Tous J, 2012) of Mira y Lopez laboratory (University of Barcelona) that transformed the measurements of drawn lines on a touch screen from pixels into millimetres. As results showed, in the proprioceptive test condition, the changes in deviations related to spatial (lineograms) or line length variability (parallels) did not reach any statistical signifi cance; while the changes in line length performance (lineograms) were found signifi cant (that corresponds to inhibition- -excitatory balance of nervous system).